Do Audit Quality Enhancements Improve Financial Reporting Credibility? A Systematic Literature Review - Yudi Basma Albahrun; Rui Lopes; Andi Kusumawati; Agus Bandang (JURNAL AKUNTANSI DAN AUDITING, 2025)
This systematic review examines whether, how, and under what conditions audit quality enhancements (AQEs) strengthen financial reporting credibility (FRQ). Following PRISMA procedures, we screened 2015–2025 studies and synthesized 25 core articles; a VOSviewer map highlights three clusters: (i) governance and audit committees, (ii) audit process and policy levers (effort, specialization, rotation/EQCR, ISQM-1/ISA 220, and KAM/CAM design), and (iii) reporting outcomes and earnings management. Overall, AQEs correlate with lower discretionary accruals, timelier loss recognition, fewer restatements, and more disciplined market reactions when risk-based procedures are deep, KAM/CAM are specific, and audit committees and internal audit are effective. Impacts rise with strong enforcement and institutional ownership but weaken under fee pressure, long tenure, or poor governance. We note fragmented FRQ proxies and call for causal designs and observable process-quality measures to isolate mechanisms. The review offers an integrated pathway linking governance and audit processes to reporting credibility and market consequences.